The International Civil Service : Redefining Its Independence - Tavadian, Alexandre, (International Law E-Books Online, Collection 2025., 2025)
This book explores the independence of international civil servants across various intergovernmental institutions. With rich historical insights and in-depth analysis, Tavadian uncovers the complex evolution of this independence, from its early days to contemporary challenges and practices. Drawing on his vast experience and meticulous research, he critically assesses the essential role of international civil service independence in ensuring effective international cooperation and proposes concrete solutions for strengthening it. An indispensable resource for scholars, policymakers, and legal practitioners, it sheds light on the nuanced dynamics that underpin the operation and integrity of international organizations.